(untitled) (Semiárida, 2023)
Robinia pseudoacacia, native to the United States of America and naturalized on various continents, is the third most cultivated fast-growing broadleaf in the world. In Argentina, cultivation for productive purposes is minimal, its local market is small, and there are few studies on its behaviour in commercial forestations. Due to the possibility of constituting a viable productive alternative, the adaptation of the species and the lack of data on its productive behaviour in the region, the aim of this contribution is to integrate different forestry-productive aspects of R. pseudoacacia. Dendrology, growth, yields, uses, pests and fungal diseases, seed production and propagation methods of the species were reviewed. Due to its plasticity and adaptation in the region, R. pseudoacacia constitutes a silvicultural alternative with a potential production of quality and multiple uses wood. Although, under proper management, the production of quality wood is promising, studies are needed on productive behaviour, management, yields, products, the real impact of pests and diseases, and market niches in the region. There are sources of local genetic material that would allow starting a breeding program from naturalized populations in the region.